2017
DOI: 10.1186/s12916-017-0917-2
|View full text |Cite|
|
Sign up to set email alerts
|

Gestational hypertensive disorders and retinal microvasculature: the Generation R Study

Abstract: BackgroundChanges in the microvasculature associated with pre-eclampsia and gestational hypertension have been proposed as a potential pathway in the development of cardiovascular disease. We examined whether gestational hypertensive disorders, such as pre-eclampsia and gestational hypertension, are related to the maternal retinal microvasculature status after pregnancy.MethodsThis study is part of an ongoing population-based prospective cohort study. During pregnancy and 6.2 years after the index pregnancy (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…This may be explained by the relative small number of women with twin pregnancies in our study. In previous studies performed in women with singleton pregnancies, we did find associations years after pregnancy in women with PE compared to women without PE [28,36]. However, it might also be that PE in women with twin pregnancies is potentially a different phenotype compared to PE in women with singleton pregnancies, independently from cardiovascular predisposition of mothers.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This may be explained by the relative small number of women with twin pregnancies in our study. In previous studies performed in women with singleton pregnancies, we did find associations years after pregnancy in women with PE compared to women without PE [28,36]. However, it might also be that PE in women with twin pregnancies is potentially a different phenotype compared to PE in women with singleton pregnancies, independently from cardiovascular predisposition of mothers.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, 6 and 10 years after pregnancy may not be the best moments to measure cardiovascular adaptation. However, previous studies in women with singleton pregnancies did find differences for women with PE within this time period [28,36]. Data are represented as n (%), mean (SD) or as the median with the 90% range.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The original article [1] contained an error whereby the senior author, M. Kamran Ikram’s name was mistakenly interchanged.…”
Section: Erratummentioning
confidence: 99%
“…Emerging evidence has shown that hypertensive disorders of pregnancy (HDP) are associated with postpartum microvascular changes,1 2 such as retinal arteriolar narrowing and venular widening. Since antenatal blood pressure (BP) is also known to increase a series of cardiovascular (CV) risks such as insulin resistance,3 oxidative stress and endothelial dysfunction,4 it is unclear whether previous findings of antenatal BP and postpartum microvascular alteration are mediated by CV risks.…”
Section: Introductionmentioning
confidence: 99%